Prilagajanje odmerjanja analgetikov glede na ledvično in jetrno funkcijo - Petre, Maja (Farmacevtski vestnik, 2012)
Pain is a common problem in patients with renal or liver disease. Understanding altered metabolism and excretion of analgesics in this population of patients is essential for adequate pain relief while minimizing adverse effects or toxicity. Some analgesics may also aggravate a preexisting renal or hepatic disease. This article discusses pain management in this group of patients. It outlines which analgesics are recommended and considered safe, which analgesics require dose adjustment and which should be avoided.
Keywords: Administration and Dosage; Analgesics; Analgetiki; Bolečina; jetrna funkcija; ledvična funkcija; odmerjanje zdravil; Pain; Predpisovanje in doziranje; Therapy; Zdravljenje